The conservation of brick buildings / Suhaida Manaf - Manaf, Suhaida (Faculty of Architecture, Planning and Surveying, 2014)
Construction of brick buildings is not new in building construction as it has been existed since many years ago. The buildings that are being constructed using the bricks might have their own identity and architectural style. However, the building will experience the changes as it grows over a period of time. It is important to take an action to protect the building from being destroyed physically before it worsens. In other words, those actions can be described as conserving action to the building as the actions involve making good to the building. These can be seen physically as the building facade is being protected and maintained for its appearance and function. Development of bricks building has been established since hundred years ago which every building has its own identity. Each building constructed will show the identity of surrounding culture and the time it was being constructed. However, the building that grew through a period of time will undergo the changes that can be seen physically. Hence the buildings need to be conserve so that the building can have longer life time performance. Conserving bricks building is not easy as it has some restrictions in achieving the purpose of the conservation. The bricks behavior itself contributes to the restriction. For instance, the bricks are a porous material which can permits water movement into the bricks. In a long term period, the water can penetrate into internal wall, which is one of the building problems.